Green polymer chemistry and composites : pollution prevention and waste reduction - Rawat, Neha Kanwar; Stoica, Iuliana; Haghi, A. K. (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"This new book examines the latest developments in the important and growing field of producing conventional polymers from sustainable sources. With recent advancements in synthesis technologies and the discovery of new functional monomers, research shows that green polymers with better properties can be produced from renewable resources. This volume describes these advances in synthesis, processing, and technology and provides not only state-of-the-art information but also acts to stimulate research in this direction. Green Polymer Chemistry and Composites: Pollution Prevention and Waste Reduction illustrates how chemical industries play an essential role to sustain the world economies and looks at forthcoming technologies and scientific developments in novel products, less toxicological materials, and industrial procedures with high efficiency and renewable energy products. Green chemistry seeks for the design of innovative chemical products with higher efficiency and lowest hazardous substances for the health and the environment. This book offers an excellent resource for researchers, upper-level graduate students, brand owners, environment and sustainability managers, business development and innovation professionals, chemical engineers, plastics manufacturers, biochemists, and suppliers to the industry to debate sustainable, economic solutions for polymer synthesis."--
Green Chemistry and Sustainable Nanotechnological Developments: Principles, Designs, Applications, and Efficiency / Yassine Slimani and Essia Hannachi -- The Next Generation Sustainable Polymers / Abu Darda, Halima Khatoon, Mohd Irfan, Sameer Ahmad, Weqar Ahmad Siddiqi, Sajid Iqbal, Ashiq Hussain Pandit, and Mohd Danish Ansari -- An Efficient Self-Charging Photocapacitor for Integrated Energy Storage and Conversion / Shama Islam, Zubair Aslam, Halima Khatoon, Hana Khan, and Mohd Zulfequar -- Polylactic Acid: An Eco-Friendly Material in the Packaging Industry, Paving the Way Toward a Greener Environment / S. Roopa, B. Sowmya, S. Preethi, and Arul Maximus Rabel -- Organic Materials for Green Electronics / Vidya G., Saravanan Subbiahraj, and Praveen C. Ramamurthy -- Natural Oil-Based Polymer: A Sustainable Approach Toward Green Chemistry / Taruna Singh and Athar Adil Hashmi -- Renewable Resource-Based Environmental Friendly Waterborne Polymeric Anticorrosive Nanocomposite Coatings / Mohd Irfan, Halima Khatoon, Rabia Kouser, Abu Darda, Shahidul Islam Bhat, and Sajid Iqbal -- An Approach for Development of Materials for Green Chemical Catalytic Processes: Green Catalysis / Rimzhim Gupta, Akanksha Adaval, and Sushant Kumar -- Bionanocomposites, Biofuels, and Environmental Protection: A Far-Reaching Review and the Visionary Future / Sukanchan Palit -- Perspectives for Electronic Nose Technology in Green Analytical Chemistry / T. Sonamani Singh, Priyanka Singh, and R.D.S. Yadava -- Multiphase Materials Based on Green Polymers for Electronics with Minimized Environmental Impact / Andreea Irina Barzic -- Sustainable Eco-Friendly Polymer-Based Membranes Used in Water Depollution for Life-Quality Improvement / Adina Maria Dobos, Mihaela Dorina Onofrei, and Anca Filimon.
OCLC-licensed vendor bibliographic record.
Keywords: Polymers; Polymerization; Green chemistry; Sustainability; SCIENCE / General; TECHNOLOGY / Engineering / Chemical & Biochemical